Advances in biological and medical physics. - Hamilton, Joseph G. (Joseph Gilbert), 1907-; Lawrence, John H. (John Hundale), 1904-1991 (Academic Press Inc., 1948)
Advances in Biological and Medical Physics, Volume 1, provides an overview of the state of knowledge in biological and medical physics. The book contains 10 chapters and opens with a discussion of methods by which isotopes can be employed in medical and biological problems, and the factors that influence the choice of isotopes that have been and may be used in biological work. This is followed by separate chapters on the applications of nitrogen and carbon isotopes to in vivo studies of the animal organism; the nature and production of artificial radioactivity; the interaction of radioactivity.